Current Issues of Inbound Tourism in the Republic of Kazakhstan and Ways of Promotion - AYETOV, Sayat; URUZBAYEVA, Nazym (Journal of Environmental Management and Tourism, 2019)
This article analyzes the current state of inbound tourism in the Republic of Kazakhstan, the authors carried out a sociological analysis that identified the main problems hampering the development of inbound tourism in Kazakhstan and proposed the solution of infrastructure problems through the establishment of a lending institution.